Beyond Axon Guidance: Roles of Slit-Robo Signaling in Neocortical Formation - Gonda, Yuko; Namba, Takashi; Hanashima, Carina (Frontiers in Cell and Developmental Biology, 2020)
The formation of the neocortex relies on intracellular and extracellular signaling molecules that are involved in the sequential steps of corticogenesis, ranging from the proliferation and differentiation of neural progenitor cells to the migration and dendrite formation of neocortical neurons. Abnormalities in these steps lead to disruption of the cortical structure and circuit, and underly various neurodevelopmental diseases, including dyslexia and autism spectrum disorder. In this review, we focus on the axon guidance signaling Slit-Robo, and address the multifaceted roles of Slit-Robo signaling in neocortical development. Recent studies have clarified the roles of Slit-Robo signaling not only in axon guidance but also in progenitor cell proliferation and migration, and the maturation of neocortical neurons. We further discuss the etiology of neurodevelopmental diseases, which are caused by defects in Slit-Robo signaling during neocortical formation.